2018
DOI: 10.1007/s00204-018-2215-y
|View full text |Cite
|
Sign up to set email alerts
|

Levels of selected analytes in the emissions of “heat not burn” tobacco products that are relevant to assess human health risks

Abstract: Consumers of combustible cigarettes are exposed to many different toxicologically relevant substances associated with negative health effects. Newly developed “heat not burn” (HNB) devices are able to contain lower levels of Harmful and Potentially Harmful Constituents (HPHCs) in their emissions compared to tobacco cigarettes. However, to develop toxicological risk assessment strategies, further independent and standardized investigations addressing HPHC reduction need to be done. Therefore, we generated emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
110
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 136 publications
(124 citation statements)
references
References 20 publications
7
110
0
7
Order By: Relevance
“…Independent studies by Farsalinos et al [9] and Bekki et al [21] showed that IQOS sticks contained 70-80% of the nicotine concentration found in conventional cigarettes. Davis and to determine the composition of, and the potential health risk from, the polymer-film filter of IQOS sticks 4 IQOS devices, IQOS sticks (strong menthol); 5 running conditions incorporating 2 different cleaning protocols; a visual and stereomicroscopic inspection of IQOS sticks pre-use and post-use to determine the extent of tobacco plug charring (from pyrolysis) and polymer-film filter melting, and to elucidate the effects of cleaning on charring; unused polymer-film filters were evaluated by gas chromatographymass spectrometry headspace analysis to determine emissions of potential toxic chemicals during filter heating -the use of 1 IQOS stick left a significant amount of debris, fluid and fragments of cast-leaf in the device holder the implementation of manufacturer's cleaning instructions increased charring of the tobacco plug and melting of the polymer-film the heat produced by the device was enough to cause charring of the tobacco plug via pyrolysis and melting of the polymer-film filter formaldehyde cyanohydrin was released from the polymer-film filter at 90°C (which is well below the maximum temperature reached during normal usage) [25] and (2017) [26] to evaluate emissions of submicronic particles (SMPs) arising from the "real use" of a conventional cigarette, a hand-rolled cigarette, an e-cigarette, and IQOS, as well as to estimate the dose of SMPs deposited in the respiratory system of individuals (3 months to 21 years of age) exposed to secondhand smoke 4 adult smokers, aged 37-60; a model smoking room 52.7 m2, 3 smoking sessions (1 cigarette or IQOS stick each) with 1-h intervals for each smoking device; doses deposited in the respiratory system of passive smokers were estimated using a multiple-path particle dosimetry model -both tested non-combustion devices (an e-cigarette and IQOS) emitted submicronic particles particle emissions from IQOS were higher than from an e-cigarette during IQOS use, 1-h interval between sessions, particle values were higher, compared to the baseline, during e-cigarette use, 1-h intervals between sessions were sufficient to allow particle decay to reach baseline values an estimated uptake of passive smokers decreased with age; higher doses were estimated for traditional cigarettes compared to non-combustion devices a reduction of harmful constituents results from the lower temperature of HTPs during their use, rather than from the heating stick ingredients [33] chemical evaluation of smoke generated during IQOS use with the contents of smoke from conventional cigarettes emission of a commercially available HTP (IQOS), following the HCI regime; analysis of the particulate matter (TPM), nicotine, water, aldehydes, and other volatile organic compounds (VOCs); a linear smoking machine, 12 puffs (4 intervals of 3 puffs each) -nicotine yield was comparable to traditional combustible cigarettes a substantial reduction in the levels of aldehydes (approx. 80-95%) and VOCs (approx.…”
Section: Chemical Composition Of Tobacco Sticksmentioning
confidence: 92%
See 3 more Smart Citations
“…Independent studies by Farsalinos et al [9] and Bekki et al [21] showed that IQOS sticks contained 70-80% of the nicotine concentration found in conventional cigarettes. Davis and to determine the composition of, and the potential health risk from, the polymer-film filter of IQOS sticks 4 IQOS devices, IQOS sticks (strong menthol); 5 running conditions incorporating 2 different cleaning protocols; a visual and stereomicroscopic inspection of IQOS sticks pre-use and post-use to determine the extent of tobacco plug charring (from pyrolysis) and polymer-film filter melting, and to elucidate the effects of cleaning on charring; unused polymer-film filters were evaluated by gas chromatographymass spectrometry headspace analysis to determine emissions of potential toxic chemicals during filter heating -the use of 1 IQOS stick left a significant amount of debris, fluid and fragments of cast-leaf in the device holder the implementation of manufacturer's cleaning instructions increased charring of the tobacco plug and melting of the polymer-film the heat produced by the device was enough to cause charring of the tobacco plug via pyrolysis and melting of the polymer-film filter formaldehyde cyanohydrin was released from the polymer-film filter at 90°C (which is well below the maximum temperature reached during normal usage) [25] and (2017) [26] to evaluate emissions of submicronic particles (SMPs) arising from the "real use" of a conventional cigarette, a hand-rolled cigarette, an e-cigarette, and IQOS, as well as to estimate the dose of SMPs deposited in the respiratory system of individuals (3 months to 21 years of age) exposed to secondhand smoke 4 adult smokers, aged 37-60; a model smoking room 52.7 m2, 3 smoking sessions (1 cigarette or IQOS stick each) with 1-h intervals for each smoking device; doses deposited in the respiratory system of passive smokers were estimated using a multiple-path particle dosimetry model -both tested non-combustion devices (an e-cigarette and IQOS) emitted submicronic particles particle emissions from IQOS were higher than from an e-cigarette during IQOS use, 1-h interval between sessions, particle values were higher, compared to the baseline, during e-cigarette use, 1-h intervals between sessions were sufficient to allow particle decay to reach baseline values an estimated uptake of passive smokers decreased with age; higher doses were estimated for traditional cigarettes compared to non-combustion devices a reduction of harmful constituents results from the lower temperature of HTPs during their use, rather than from the heating stick ingredients [33] chemical evaluation of smoke generated during IQOS use with the contents of smoke from conventional cigarettes emission of a commercially available HTP (IQOS), following the HCI regime; analysis of the particulate matter (TPM), nicotine, water, aldehydes, and other volatile organic compounds (VOCs); a linear smoking machine, 12 puffs (4 intervals of 3 puffs each) -nicotine yield was comparable to traditional combustible cigarettes a substantial reduction in the levels of aldehydes (approx. 80-95%) and VOCs (approx.…”
Section: Chemical Composition Of Tobacco Sticksmentioning
confidence: 92%
“…80-95%) and volatile organic compounds (approx. 97-99%) in the IQOS aerosol compared to cigarette smoke [33]. Pacitto et al also showed lower volatile and non-volatile particle concentrations in the mainstream IQOS aerosols compared to traditional cigarette smoke [20].…”
Section: Chemical Composition Of Tobacco Sticksmentioning
confidence: 96%
See 2 more Smart Citations
“…Gehalte an ausgesuchten Analyten im Hauptstromrauch eines Tabakerhitzers und konventioneller Zigaretten. Es sind jeweils die höchsten und niedrigsten Werte angegeben, die von Mallock et al[15] in 2 verschiedenen Sorten Tabaksticks sowie von Counts et al[18] in konventio-nellenZigarettengefundenwurden.InSpalte5istdieReduktionderAnalytenimHauptstromrauch des Tabakerhitzers im Vergleich zu konventionellen Zigaretten in % dargestellt…”
unclassified